Use of subepithelial conjunctive tissue graft in root covering - Denis Clemente Rodrigues; Ricardo Alves; Takeshi Kato Segundo (Faculdade São Leopoldo Mandic, 2010)
Gingival recession may cause cosmetic changes and root hypersensitivity, which can alter mastication and tooth brushing, and thus contribute to the progression of periodontal disease. Treatment of gingival recessions with subepithelial conjunctive tissue grafting is very predictable due to its bilaminar nature. However, some factors may influence the success of the procedure, among them: selection of the lesion; characteristics of the defect with regard to the depth and width of the recession, the deeper and wider the recession, the worse the prognosis, and also the presence of restorations. Furthermore, it is necessary to control the etiologic factors of recessions, such as inflammation and traumatic brushing, control of systemic factors, occlusal trauma, smoking and harmful habits, technical considerations and asepsis. The success of the procedure must be based on observing the possible factors that might influence their predictability, as well as respecting the basic principles of mucogingival surgery.